Point‐of‐care HIV early infant diagnosis: is test sensitivity everything?. Issue 1 (4th September 2015) - Dunning, Lorna; Hsiao, Nei‐yuan; Myer, Landon
Abstract : Despite improvements in PMTCT services in low‐ and middle‐income countries, there are still almost 200, 000 new paediatric HIV infections annually in sub‐Saharan Africa. This has led to early infant HIV diagnosis (EID) programmes becoming a public health priority, but until recently, EID has required specialist laboratory equipment and trained personnel which is only feasible in urban, centralized facilities. It is thought that the successful implementation of a point‐of‐care (POC) test for EID has the potential to increase access to virological tests and address some of the barriers regarding retention of infants in care. However, POC evaluation has not integrated focus on performance characteristics with the health systems issues surrounding the adoption of and optimum use of these new technologies. We propose that moderate improvements in linkage to care can more than offset suboptimal sensitivity of a POC EID test which could be critical in adjusting the focus for EID programme management away from test performance and towards their ability to facilitate successful linkage to antiretroviral therapy (ART) services. These findings also highlight the urgent need to explore the implementation and operational aspects of emerging POC tests in order to fully realize the potential benefits of new technologies in practice.